Surface Potential of 1-Hexanol Solution: Comparison with Methyl Isobutyl Carbinol - Nguyen, Cuong; Phan, Chi; Ang, Ha Ming; Nakahara, H.; Shibata, O.; Moroi, Y. (American Chemical Society, 2013)
Alcohols have an amphiphilic characteristic and are employed in industrial processes to enhance interfacial properties. In this study, the change in surface potential (ΔV) and surface tension of 1-hexanol were measured on the subsurface of electrolyte solutions (NaCl at 0.02, 0.2, and 2 M). The results were fitted by a newly proposed model, which includes the influence of electrolytes and surface concentration of surfactant at the air-water interface. The findings were compared to those of a previous study on methyl isobutyl carbinol (MIBC). Most significantly, the modeling results showed opposite behaviors between the two systems: adsorbed MIBC enhances the presence of cations, whereas adsorbed 1-hexanol enhances the presence of anions. The difference highlights thesignificance of the molecular structure on the arrangement at the air/ water interface.